Investigation into the microwave power absorption in tissues - Raad Hamdan Thaher; Heba Hadi Ali; Isam Salah Hameed (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, the behavior of different tissues to microwave signal is presented. Beef, lamp, and fat were taken as tissue samples. The three types of tissues were taken in three different cases as soaked, normal, and dried. Moreover, each individual sample was prepared in five thickness as 1mm, 2mm, 3mm, 4mm and 5mm in the x-band frequency. The objectives of this paper were discussed to determine the power absorption when each sample is tested. The experimental results showed the soaked meat as the most power absorbing state when compared to the other cases of the normal and dried samples for the same thickness value.  It has been found that the microwave power absorption is directly proportional to the thickness. Besides, the relationship between the microwave power absorption and the distance between transmitting and receiving antenna was also taken in consideration. It was found that as long as the tested sample is far away from the transmitter, the attenuation of the transmitted energy increases. With the aid of two techniques represented by an insertion transmission method and free-space transmission method, this paper presented an insight about the relation between the (moisture, distance, and thickness) and the microwave power absorption.